2012
DOI: 10.22201/ib.20078706e.2012.2.1246
|View full text |Cite
|
Sign up to set email alerts
|

Nuevos registros del género Fomitiporia (Hymenochaetales, Basidiomycota) en México

Abstract: Six species of the genus Fomitiporia are described and illustrated for the first time from Mexico and they are F. apiahyna, F. calkinsii, F. dryophila, F. langloisii, F. maxonii y F. texana; F. sonorae is reported from Querétaro State. The specimens are deposited in the Herbaria CESUES, ENCB, FCME, IBUG, ITCV, MEXU, UJAT, UNL, UJED from Mexico and MUCL and proceed from 18 states of the Mexican Republic. Besides, a distribution map of the species is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 17 publications
1
18
0
2
Order By: Relevance
“…The best evolutionary models estimated for the alignments were T92+G+1 for the Fomitiporia dataset and K2+G+I for Fuscoporia dataset. Notes.-Fomitiporia maxonii has a perennial and resupinate basidiomata with a sterile margin, corky to woody, hymenophore with circular to ellipsoid or oblique pores, 7-9 per mm, hyphal system dimitic with hymenial setae absent, basidiospores subglobose to globose, (4.5-)5.3-6.5(-7) × (4-)4.8-6(-6.7) μm, and hyaline rhomboid crystals abundant in the hymenium as an important feature (Raymundo et al, 2012). Fomitiporia maxonii is reported from Argentina (Raymundo et al, 2012), Belize (Ryvarden, 2004;Raymundo et al, 2012), Brazil (Raymundo et al, 2012), Costa Rica (Ryvarden, 2004;Decock et al, 2007), Cuba (Decock et al, 2007;Raymundo et al, 2012), Ecuador (Ryvarden, 2004;Raymundo et al, 2012), Jamaica (Decock et al, 2007;Raymundo et al, 2012), Mexico (Raymundo et al, 2012), USA (Vlasák et al, 2011), and Venezuela (Decock et al, 2007;Raymundo et al, 2012), being in Brazil reported in the North, Northeast, Southeast and South regions, as well as for the states studied here (Flora e Funga do Brasil, 2022; Species Link, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The best evolutionary models estimated for the alignments were T92+G+1 for the Fomitiporia dataset and K2+G+I for Fuscoporia dataset. Notes.-Fomitiporia maxonii has a perennial and resupinate basidiomata with a sterile margin, corky to woody, hymenophore with circular to ellipsoid or oblique pores, 7-9 per mm, hyphal system dimitic with hymenial setae absent, basidiospores subglobose to globose, (4.5-)5.3-6.5(-7) × (4-)4.8-6(-6.7) μm, and hyaline rhomboid crystals abundant in the hymenium as an important feature (Raymundo et al, 2012). Fomitiporia maxonii is reported from Argentina (Raymundo et al, 2012), Belize (Ryvarden, 2004;Raymundo et al, 2012), Brazil (Raymundo et al, 2012), Costa Rica (Ryvarden, 2004;Decock et al, 2007), Cuba (Decock et al, 2007;Raymundo et al, 2012), Ecuador (Ryvarden, 2004;Raymundo et al, 2012), Jamaica (Decock et al, 2007;Raymundo et al, 2012), Mexico (Raymundo et al, 2012), USA (Vlasák et al, 2011), and Venezuela (Decock et al, 2007;Raymundo et al, 2012), being in Brazil reported in the North, Northeast, Southeast and South regions, as well as for the states studied here (Flora e Funga do Brasil, 2022; Species Link, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Fomitiporia impercepta differs by smaller basidiospores (4.0)5.0-6.0(7.0) × 4.0-6.0(7.0) μm (Campos-Santana et al, 2014;Morera et al, 2017;Rajchenberg et al 2019). Fomitiporia langloisii has a paler pore surface, grayish and honey-colored, sometimes with a slight pinkish tinge in young specimens, while F. neotropica commonly has a pore surface yellowish brown, greyish brown, dark yellow to dark brown or greyish chocolate brown (Decock et al, 2007;Raymundo et al, 2012;Campos-Santana et al, 2014). Decock et al (2007) suggested that F. langlosi is an older available name for F. hesleri.…”
Section: Vouchermentioning
confidence: 99%
See 1 more Smart Citation
“…y contexto color marrón, con sistema hifal dimítico con las setas himeniales con esporas globosas a sub-globosas. Las especies de este género crecen sobre madera de árboles vivos o muertos en gimnospermas y angiospermas, se distribuyen en regiones templadas y tropicales de todo el mundo y ocasionan una pudrición blanca (Raymundo et al 2012). Fomitiporia sp.…”
Section: Discussionunclassified
“…Macrofungi presenting resupinate, effused-reflexed or pileate basidiomata, a poroid hymenophore with or without hymenial setae, a dimitic hyphal system, and cynophylous, dextrinoid, and thick-walled basidiospores were reclassified as Fomitiporia (Fischer 1996;Decock et al 2005Decock et al , 2007. Species of this genus grow on wood of both live and dead trees in temperate or tropical regions and cause white rot (Fischer 2002;Raymundo et al 2012;Cloete et al 2014;Ota et al 2014).…”
Section: Introductionmentioning
confidence: 99%